Conservation Induced Displacement and Resettlement : a Case Study of Gujjar Rehabilitation from Rajaji National Park - Mishra, B. K.; Badola, Ruchi; Bhardwaj, A. K. (Indian Forester, 2007)
Involuntary displacement of people from their productive assets and homesteads, caused due to industrial and infrastructure projects, and more recently for creation of Wildlife Protected Areas (Pas) has faced wide spread criticism. Once displaced, the affected families are pushed into an open-market situation as individuals competing for their survival in a hostile new environment. A majority of them prove to be losers in this new race of development. Thus, such efforts have been widely criticized for the adverse impact they have had on the local people who have been relocated as a consequence of such projects. In general there is now some consensus on the fact that there are inadequacies in the relocation process and package, and identification of better strategies to deal with it are being called for. However, there are also some recent initiatives of voluntary relocation in some PAs of the country which seem to have captured lessons from the past and thus, these initiatives provide an opportunity to examine relevant issues and the reasons for their success. There is a paucity of studies on systematic documentation of 'wise and bad' practices of village relocation program from the PAs. Therefore, this paper attempts to document the process and package of community relocation and rehabilitation program implemented recently in Rajaji National Park, Uttarakhand.